Analysis of a Multilevel Voltage-Based Coordinating Controller for Solar-Wind Energy Generator: A Simulation, Development and Validation Approach - Lachumanan , T.; Singh, R.; Shapiai, M. I.; Anand, T. J. S. (Engineering, Technology & Applied Science Research, 2021)
This paper presents the development and the performance analysis of the developed model of a voltage-based coordinating controller. This model is developed to perform activities such as sensing, measuring, switching, coordinating, and effectively managing the output voltages produced by the solar-wind renewable energy sources in order to supply the connected load or/and charge the battery storage system. The developed model has different tasks to perform when solar-wind energy sources both produce output voltages simultaneously, also contributing to solving the requirements of different synchronization algorithms for a multi-agent renewable energy system. The sensed and measured output voltages of the solar-wind energy sources are used as directive information to allow the developed model’s controller to supply the available power to the connected load or/and charge the battery storage system. Also, the produced information at the model’s controller input is used to individually control the other sub-system, which directly assists in achieving the aim of simultaneous operation when both solar and wind energy sources produce output voltages. The model is developed and simulated in Matlab/Simulink. The simulation results are used to validate the developed methodology and the aims of the developed model.